2016
DOI: 10.1212/wnl.0000000000003125
|View full text |Cite
|
Sign up to set email alerts
|

MR parkinsonism index predicts vertical supranuclear gaze palsy in patients with PSP–parkinsonism

Abstract: Objective:To identify a biomarker for predicting the appearance of vertical supranuclear gaze palsy (VSGP) in patients affected by progressive supranuclear palsy–parkinsonism (PSP-P).Methods:Twenty-four patients with PSP-P were enrolled in the current study. Patients were clinically followed up every 6 months until the appearance of VSGP or the end of the follow-up (4 years). Participants underwent MRI at baseline and at the end of follow-up. Magnetic resonance parkinsonism index (MRPI), an imaging measure use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 38 publications
2
44
0
1
Order By: Relevance
“…45 The pons/midbrain ratio, as calculated from conventional MRI, had high specificity and sensitivity for the diagnosis of pathologically confirmed PSP. 46 In studies of the early stages of PSP, 46 MRPI was also able to predict development of PSP-RS in unclassifiable parkinsonism and eye movement abnormalities in PSP-P. 45,47 …”
Section: Biomarkers (Table 1)mentioning
confidence: 99%
“…45 The pons/midbrain ratio, as calculated from conventional MRI, had high specificity and sensitivity for the diagnosis of pathologically confirmed PSP. 46 In studies of the early stages of PSP, 46 MRPI was also able to predict development of PSP-RS in unclassifiable parkinsonism and eye movement abnormalities in PSP-P. 45,47 …”
Section: Biomarkers (Table 1)mentioning
confidence: 99%
“…Similarly, another autopsy study found that midbrain atrophy was present in only 86.4% of pathologically confirmed PSP, and the hummingbird sign was only present in 68.4%, even after a disease duration of 4.8 years . However, midbrain atrophy has been observed in speech and language disorders that are confirmed or suspected of having PSP pathology, as well as in PSP‐F and PSP‐P . Midbrain atrophy in vPSP is typically less severe than in PSP‐RS, although there is some suggestion that abnormalities on the MRPI could be an early feature in PSP‐P and have some value as a level 3 biomarker.…”
Section: Structural Mrimentioning
confidence: 99%
“…Magnetic resonance (MR) imaging measurements have been shown to be useful for diagnosing PSP . The MR Parkinsonism Index (MRPI) has proven to be an accurate biomarker for diagnosing patients with PSP and for predicting the clinical evolution toward PSP phenotypes of patients affected by undetermined parkinsonism or the appearance of vertical supranuclear gaze palsy (VSGP) in patients with PSP‐P . Overall, this biomarker is highly accurate in diagnosing PSP‐RS but shows a low sensitivity in distinguishing between patients with PSP‐P and those with PD .…”
mentioning
confidence: 99%
“…Magnetic resonance (MR) imaging measurements have been shown to be useful for diagnosing PSP. 12,13 The MR Parkinsonism Index (MRPI) has proven to be an accurate biomarker for diagnosing patients with PSP [14][15][16][17][18][19][20][21][22][23][24][25][26] and for predicting the clinical evolution toward PSP phenotypes of patients affected by undetermined parkinsonism 27,28 or the appearance of vertical supranuclear gaze palsy (VSGP) in patients with PSP-P. 29 Overall, this biomarker is highly accurate in diagnosing PSP-RS 12 but shows a low sensitivity in distinguishing between patients with PSP-P and those with PD. 18,26,30 Recently, we demonstrated that a new version of MRPI that included the measurement of third ventricle width (MRPI 2.0) was highly accurate in differentiating PSP-P patients from PD.…”
mentioning
confidence: 99%